2006
DOI: 10.1038/sj.leu.2404409
|View full text |Cite
|
Sign up to set email alerts
|

Activating mutations in NOTCH1 in acute myeloid leukemia and lineage switch leukemias

Abstract: Activating mutations in NOTCH1 are found in over 50% of human T-cell lymphoblastic leukemias (T-ALLs). Here, we report the analysis for activating NOTCH1 mutations in a large number of acute myeloid leukemia (AML) primary samples and cell lines. We found activating mutations in NOTCH1 in a single M0 primary AML sample, in three (ML1, ML2 and CTV-1) out of 23 AML cell lines and in the diagnostic (myeloid) and relapsed (T-lymphoid) clones in a patient with lineage switch leukemia. Importantly, the ML1 and ML2 AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 18 publications
4
48
0
Order By: Relevance
“…T-ALL is a malignant tumor characterized by the aberrant activation of oncogenic TFs (13). We recently demonstrated that constitutive activation of NOTCH1 signaling due to mutations in the NOTCH1 gene activates a transcriptional network that controls leukemic cell growth (11,(14)(15)(16). These studies also demonstrated a fundamental role for HES1 and MYC as transcriptional mediators of NOTCH1 signals (15,17).…”
Section: Resultsmentioning
confidence: 97%
“…T-ALL is a malignant tumor characterized by the aberrant activation of oncogenic TFs (13). We recently demonstrated that constitutive activation of NOTCH1 signaling due to mutations in the NOTCH1 gene activates a transcriptional network that controls leukemic cell growth (11,(14)(15)(16). These studies also demonstrated a fundamental role for HES1 and MYC as transcriptional mediators of NOTCH1 signals (15,17).…”
Section: Resultsmentioning
confidence: 97%
“…Modulation of Notch as a means of targeting cancer stem cells is well reviewed (Rizzo et al 2008). In addition, oncogenic mutation of Notch has been recognized as a key event in the pathogenesis of certain cancer types, notably T-cell acute lymphoblastic leukemia (T-ALL) (Weng et al 2004;Palomero et al 2006). Though Notch signaling modulation may be an effective tool in all of these scenarios, this article will focus on the involvement of Notch in tumor angiogenesis, and efforts directed at inhibiting this facet of its activity.…”
Section: Tips Stalks and Tubesmentioning
confidence: 99%
“…3,4 Microarray technology for genome-wide expression profiling has been successfully applied to the classification and biology of both precursor-B-ALL and T-ALL and subtypes thereof. [8][9][10][11][12][13][14][15][16][17][18] Microarray technology can also provide an unbiased means to identify genes involved in the emergence of resistant leukemic clones. [5][6][7] For the identification of molecular mechanisms involved in relapse of ALL, pairwise comparison of matched diagnosis and relapses is, in principle, the most straightforward way to identify such genes.…”
Section: Introductionmentioning
confidence: 99%